ASSESSMENT OF VULNERABILITY RESULTING FROM PROJECTED CLIMATE CHANGE ON THE LIVELIHOOD OF ORASHI FARMERS IN NIGER DELTA REGION OF NIGERIA - Cookey, A. T.; Unaeze, H. C. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study was conducted to assess the vulnerability resulting from projected climate change and the rate of intervention by various institutions on the livelihood of Orashi framers in Niger Delta region of Nigeria. Purposive sampling technique was used to select 100 respondents. Data were collected using structured questionnaire and analysed using both descriptive and inferential statistics. The findings revealed that on the socio-economic characteristics of displaced persons and institutions, 52% of the climate refugees were female. 90% of the farms were all in rural areas. 38% were within the age of 40-49 years, Approximately 50% had spent 6 years in school and the majority 57% had a household size of 4-7 persons, 38% had 1-3 persons, 3% had within 8-11 persons while 2% had above 11 persons. Going further the result on the Institution’s socioeconomic characteristics reveals that the majority of the Institutions are public and are locally based with a staff strength of above 30 persons On socio-economic characteristics as they affect their response to agricultural productivity using the probit model shows that because they are displaced and currently in a displaced camp their response towards their livelihood is low.. The vulnerability category vulnerability category of 0.148-0.167 placed Ahoada West LGA as the most vulnerable landscape. Similarly, the vulnerability range of 0.144-0.148 placed Abua and Ahoada East LGAs as moderately vulnerable landscape. In contrast, the vulnerability range of 0.001-0.144 placed Ogba Egbema Ndoni LGA as less vulnerable landscape. The study concluded that Institutions are the media through which external intervention reinforce and that local institutions play a key role in shaping the extent to which communities became vulnerable and respond to environmental risks. Therefore the study recommended that to help maintain cultural identity, community, and dignity, it would seem more just to attempt to relocate refugees who chose that option such that they are relocated to places where they will be together with member of their family, community, and broader and Government should design a multi-sectorial approach so as to build the capacity of Institutions in order to address the issue of climate refugees.